Implementasi Literasi Budaya dan Kewargaan dalam Mengembangkan Berkebhinekaan Global Di SDN Bahagia 06 Kabupaten Bekasi - Fara Diba Catur Putri; Nina Nurhasanah (Publikasi dan UKI Toraja Press Universitas Kristen Indonesia Toraja, 2023)
The purpose of this journal is to investigate the implementation of cultural literacy and citizenship in developing global diversity in elementary schools (SD). In the current era of globalization, it is important for children to develop a deep understanding of cultural diversity and global citizenship. Implementation of cultural literacy and citizenship in elementary schools can help students understand cultural differences, respect diversity, and become responsible global citizens. This journal uses a qualitative research approach using the case study method. Data was collected through class observations, interviews with teachers, and analysis of documents related to the school curriculum. The participants in this study were teachers and students from several elementary schools who applied a global diversity approach. The collected data were analyzed using content analysis techniques. The results of this study indicate that the implementation of cultural literacy and citizenship in elementary schools can increase students' understanding of cultural diversity and global citizenship. Teachers play a crucial role in guiding students to develop an attitude of openness, tolerance and respect for cultural differences. They use various teaching strategies, such as collaborative activities, use of multimedia resources, and group discussions, to raise students' awareness of global diversity. In addition, the school curriculum plays an important role in integrating cultural literacy and citizenship. Learning is carried out through various subjects, such as Indonesian Language, Science, and Cultural Arts.